Utilização e consumo de água em um abatedouro - frigorífico de bovinos e avaliação microbiológica da carcaça - Claudia Ferreira Viana (2018)
The aim of the present paper was to evaluate and characterize the use and consumption of water in a slaughterhouse in the state of Minas Gerais under Federal inspection and to analyse the microbiological quality of the bovine carcass at the end of the industrial processing. Measurements of water consumption were made in the slaughter room and adjacent sectors for comparison with the total consumption for slaughtering. The average water consumption in the establishment was 1060 litres/slaughtered bovine higher than the legal recommendation, which is 800 litres/bovine. There were several points of leakage in the slaughter room and adjacent dependencies, which amounted to 24 liters/hour. On the other hand, the industry reused the condensation water from the cooling chamber to wash the external structures showing concern with water expenditure. The microbiological analysis of the carcass in the cold chamber revealed the presence of psychrotrophic microorganisms such as Pseudomonas aeruginosa and indicators such as Enterobacter cloacae, Klebisiella pneumoniae and Serratia marcescens. In addition to these microorganisms, a positive sample for Salmonella ssp. was detected and confirmed using proteomics analysis by MALDI-TOF mass spectrometry. Mesophilic microorganisms countings averaged 7,63 x 10² which indicates the proper functioning of the cooling chamber inhibiting much of the mesophilic microorganisms that could develop in the carcass. Among the strategies for reducing water consumption in the industry are the installation of timers and flow reducers in the taps of greater consumption and rumen opening using industrial auger instead of water.